ERRORS IN PRONOUNCING INTERDENTAL CONSONANTS BY AMERICAN BRITISH INSTITUTE STUDENTS YOGYAKARTA - Maulana, Adam; Maharani, Dinda Aulia; Viryanti, Rigita Ratna; Amalia, Nurul Rezky (Prologue: Journal on Language and Literature, 2026)
This research aims to find out (1) pronunciation errors produced by American British Institute students when pronouncing interdental consonant sounds, (2) factors that influenced errors in producing interdental sounds of American British Institute students, and (3) strategies implemented by the students of American British Institute to improve their pronunciation, especially in producing interdental sounds. This research used a qualitative approach. The data were shown by a descriptive qualitative method. The data were collected by transcribing the data and interview. Subjects of this research were eight students of the American British Institute, Yogyakarta. The findings of this research are (1) Pronunciation errors made by American British Institute students Yogyakarta are pre-systematic, systematic, and post-systematic; (2) Factors that influence their pronunciation are their native language in which it causes the replacement of interdental consonant [ð] and [θ] into [d̪] or [t]; the respondents’ age that makes them hard to understand English pronunciation and thus making some errors; and the instructional language, the teachers who taught in Bahasa Indonesia tend to make the students ignore about their errors; (3) Strategies that are implemented to improve their pronunciation errors are watching English movie, listening to English songs, and talking English to peers.